Simulation of BLDC Motor Drive Systems for Electric Vehicles Using Matlab Simulink - Dániel, Nemes; Hajdu, Sándor (International Journal of Engineering and Management Sciences, 2023)
The defining scientific developments of our time would not have been possible without the use of simulations. The aim of the research is to create a simulation of a BLDC motor. When creating a simulation, great emphasis must be placed on defining the purpose of the simulation. This basically determines the structure and complexity of the model. The model discussed here was created so that an optimization task could be defined more precisely by inserting it as a sub-model into a vehicle dynamics model. Scalability was another aspect, that is, to be able to increase the accuracy of the model with measured data in the future, as well as to be able to validate it. During the research, a BLDC motor efficiency map generation program was created, as well as an environment for testing the generated data. The created system gives researchers the opportunity to use a shape-correct efficiency model when simulating a BLDC motor even without measured data. This makes it possible to discover real relationships between model parameters when performing optimization.